Migrant Construction Workers’ Demography and Job Satisfaction: A New Zealand Study - Rotimi, JOB; Ramanayaka, CDE; Olatunji, O; Rotimi, FE (Emerald, 2021)
Purpose The demand for construction-related occupations has increased consistently over many years in New Zealand (NZ). This has necessitated recourse to migrant workers to address capacity and capability requirements. Migrant construction workers hail from various backgrounds with a complex set of their needs being met through employment in NZ. Research on understanding the satisfaction levels of this category of construction workers is scarce. With recent insinuations about migrant exploitations, research investigations into this knowledge area are significant. In this study, the authors sought to establish the moderating effect of migrants' demography on the determinants of job satisfaction in NZ's construction sector. Design/methodology/approach Data were obtained from migrant construction workers of Chinese extraction through a structured questionnaire survey. From 200 questionnaires administered, 108 samples were completed by migrant construction workers involved in major projects in Auckland city, NZ. Data obtained were analysed using descriptive and inferential statistics to establish the moderating effects of their demography on job satisfaction. Findings Results from this study support the internal validity and reliability of these personal characteristics as moderators of job satisfaction for migrant construction workers. These results suggest the relevance of personal characteristics of Chinese migrants in any improvement initiatives being developed for this group of construction workers. Research limitations/implications The findings from this study contribute to the discourse on the relevance of construction migrants as a strategic alternative to addressing skill shortages within the NZ construction sector. They also provide evidence that contributes to an improved understanding of the migrant workforce to meet their aspirations and enhance their general well-being. Originality/value Although the study is ethnic-specific, the conclusions show the relevance of personal characteristics in the experiences of construction migrant workers. The study is representative of the catchment of temporary migrant workers in the construction industry in NZ. The study provides insights for organisations employing migrants about putting in place appropriate measures to enhance their satisfaction levels. Finally, this study's findings may contribute to policy initiatives on the optimal categories of migrants engaged on construction activities to derive the maximum benefits for NZ.
Keywords: Construction workers; Demography; Migrant workers; Job satisfaction